In Situ Induction of Strain in Iron Phosphide (FeP2) Catalyst for Enhanced Hydroxide Adsorption and Water Oxidation. (22nd January 2020) - Li, Guowei; Yang, Qun; Rao, Jiancun; Fu, Chenguang; Liou, Sz‐Chian; Auffermann, Gudrun; Sun, Yan; Felser, Claudia
Abstract: Carbon‐based materials have been widely used in heterogeneous catalysis because of their advantages of high surface area, thermal stability, and chemical inertness. However, their role in the catalysis is not fully understood although most studies conclude that the coupling between the carbon support and catalyst could reduce the charge transfer resistance and improve the kinetics of catalytic reactions such as water splitting. In this study, a carbon‐modified FeP2 electrocatalyst with a one‐step strategy is synthesized. The tensile strain is introduced in situ in the ab crystal plane of the FeP2 catalyst. This leads to charge redistribution between H and O atoms in the OH bonds and enhances the adsorption of reaction intermediates. In the water oxidation process, this results in a decrease in the energy barrier for the rate‐determining step, specifically, the chemical step of *OH adsorption preceded by one‐electron transfer. Benefiting from the optimized adsorption energy, the strained catalysts exhibit excellent oxygen evolution reaction (OER) activity with a low overpotential in addition to their increased stability. This study provides a new strategy for the introducing of strains in functional materials and provides new insights into the influence of carbon modification on OER activity. Abstract : Tensile strain is introduced in situ at the surface of an FeP2 electrocatalyst by carbon modification. In addition to the increased chemical stability, the existence of strain could also optimize the adsorption energy of reaction intermediates, thereby decreasing the energy barrier for the rate‐determining step.